An implementation of GAN analysis for criminal face identification system - Sarosh, Ayesha; Komali, Govindu; Battu, Vishnu Vardhan; Kocharla, Laxmaiah; Kopparavuri, Eswaree Devi; Obulesu, Ooruchintala; Mande, Praveen; Mohammad, Amanulla (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
In recent times, the criminal activities are growing at an exponential rate. For the prevention of crime, one of the main issues that are before the police are accurate identification of criminals and on the other hand the availability of police officers are not adequate. The most tedious task is tracking the suspect once a crime was committed. Over the years, several technical solutions have been presented to detect the criminals however most of them were not effective. One of the most significant characteristics for the identification of a person is face. Even identical twins have their own unique faces. Face identification is a challenging topic in computer vision because the human face is a dynamic entity with a high degree of visual variation. In this area, identification accuracy and speed are significant challenges. Hence to solve these issues, an implementation of generative adversarial network (GAN) analysis for criminal face identification system is presented. GAN is used for the identification of criminals. Recall, precision, accuracy, and F1-score are used to assess the performance of the presented technique. Compared to previous models, this model will achieve better performance for criminal face detection.